2007
DOI: 10.1111/j.1439-0426.2006.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet composition of larval and young-of-year shovelnose sturgeon in the Upper Missouri River

Abstract: Obtaining food following the transition from endogenous to exogenous feeding and during the first year of life is a critical event that strongly influences growth and survival of youngof-year fishes. For shovelnose sturgeon Scaphirhynchus platorynchus, limited information is available on food habits during the first year of life. The objective of this study was to quantify diet components of shovelnose sturgeon during the transition from endogenous to exogenous feeding and during the youngof-year life stage in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 16 publications
(20 reference statements)
5
44
0
Order By: Relevance
“…In support of this, we found that a variety of larval benthic aquatic insects comprised shovelnose sturgeon diets in the freeflowing stretch of the MMR, although this depended on season. This dominance of aquatic insects in the diet of the shovelnose sturgeon has been previously reported for the Platte River (Shuman, 2003), upper Mississippi River (Hoopes, 1960;Helms, 1974;Carlson et al, (2) 1985), and the Missouri River (Held, 1969;Modde and Schmulbach, 1977;Carlson et al, 1985;Megargle, 1997;Berry, 2002;Braaten et al, 2006;Wanner et al, 2007). Variability among seasons in diet composition likely depended on seasonal environmental conditions and patterns of invertebrate recruitment.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In support of this, we found that a variety of larval benthic aquatic insects comprised shovelnose sturgeon diets in the freeflowing stretch of the MMR, although this depended on season. This dominance of aquatic insects in the diet of the shovelnose sturgeon has been previously reported for the Platte River (Shuman, 2003), upper Mississippi River (Hoopes, 1960;Helms, 1974;Carlson et al, (2) 1985), and the Missouri River (Held, 1969;Modde and Schmulbach, 1977;Carlson et al, 1985;Megargle, 1997;Berry, 2002;Braaten et al, 2006;Wanner et al, 2007). Variability among seasons in diet composition likely depended on seasonal environmental conditions and patterns of invertebrate recruitment.…”
Section: Discussionmentioning
confidence: 74%
“…Diet composition and quantity can dramatically influence condition and thus influence reproduction. Shovelnose sturgeon diets have been quantified in several large rivers: Platte River (Shuman, 2003), upper Mississippi River (Hoopes, 1960;Helms, 1974;Carlson et al, 1985), and Missouri River (Held, 1969;Modde and Schmulbach, 1977;Carlson et al, 1985;Megargle, 1997;Berry, 2002;Braaten et al, 2006;Wanner et al, 2007). Although many shovelnose sturgeon diet studies have been completed, we are unaware of any studies that have been conducted in the MMR, which is free-flowing and geologically unique to the remainder of the Mississippi River drainage.…”
Section: Introductionmentioning
confidence: 98%
“…Following capture, individuals were measured to fork length (when a well‐defined fork was present) or total length (excluding the caudal filament; Braaten et al, ) to the nearest mm. Each individual was then preserved in 100% ethanol and stored at approximately 0°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have also evaluated diet composition of age‐0 Scaphirhynchus sturgeon (Braaten, Fuller, & McClenning, ; Civiello et al, ; Gosch et al, ; Harrison, Slack, & Killgore, ; Sechler et al, ; Sechler, Phelps, Tripp, & Garvey, ), and Gosch, Civiello, Gemeinhardt, Bonneau, and Long () found that age‐0 pallid and shovelnose sturgeon ( Scaphirhynchus platyrhynchus ) consumed similar prey items; however, relationships between prey consumption and habitat, such as depth and velocity, were not investigated. Furthermore, past research has focused on the depths and velocities at, or very near, the point of capture rather than quantifying habitats available to age‐0 Scaphirhynchus sturgeon at a variety of spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Water velocity was measured near the bottom with a Marsh-McBirney flowmeter at the middle of the each sample run. Age-0 sturgeon were measured for fork length when a well-defined fork in the caudal fin was present; however, total length (excluding the caudal filament) was also measured for small individuals lacking a well-defined fork (Braaten et al 2007). Individuals 109 mm were considered age 0 (Ridenour et al 2011) and individuals 23 mm were excluded from the depth and velocity analyses described below to minimize the potential for drifting larvae to be included in these analyses (i.e., individuals > 23 mm were considered exogenously feeding larvae).…”
Section: Methodsmentioning
confidence: 99%